EFEKTIVITAS INTERVENSI PSIKOEDUKASI DALAM MENINGKATKAN PENGENDALIAN DIRI (SELF-CONTROL) PADA REMAJA DI MTSN 2 SURABAYA - Sutanto, Tiara Putri; Bagas Ryandia Ardi Saputra (UIN Sunan Kalijaga Yogyakarta, 2023)
The background of this study was carried out by examining self-control efforts through psychoeducational services at MTsN 2 Surabaya, especially in understanding how adolescents control themselves when negative emotions appear influenced by peers, and how they try to control themselves in behavior that is in accordance with Islamic norms and teachings. This study aims to evaluate the effectiveness of psychoeducational interventions in improving self-control in adolescents in MTsN 2 Surabaya. Psychoeducation is an approach that provides understanding and psychological skills to overcome emotional and behavioral challenges, with a focus on controlling or self-control of adolescents. The intervention was carried out for one month in November by providing psychoeducational services to students. The intervention method involves the delivery of information, observation, and interviews to increase adolescents' self-awareness and self-control skills. The results showed a significant improvement in the students' self-control after the intervention. The use of the pre-test and post-test self-control goals questionnaire showed an increase in scores. This study indicates that psychoeducational interventions have succeeded in having a positive impact on improving adolescent self-control skills. Keywords: Psychoeducation, Self-Control, Behavior, Adolescent